Essays on Ayn Rand's Anthem - Mayhew, Robert (Lanham, Md. : Lexington Books, 2005)
"This is the first book-length study to explore the historical, literary, and philosophical themes of Ayn Rand's anti-utopia novella Anthem. Written in 1937 in opposition to the totalitarianism of the Soviet Union (and Nazi Germany), published in 1938 in Britain, and subsequently in a revised form in the United States in 1946, Anthem investigates the importance of the ego and freedom and explores the struggles of the individual against the state. Editor Robert Mayhew has collected a variety of essays dealing with such topics as the history behind the novella's creation, publication, and reception; its connection to other anti-utopian novels; and the significance of ego and freedom, which it portrays and defends."--BOOK JACKET.
--Anthem in manuscript : finding the words / Shoshana Milgram -- Publishing Anthem / Richard E. Ralston -- Anthem : '38 & '46 / Robert Mayhew -- Reviews of Anthem / Michael S. Berliner -- Adapting Anthem : projects that were and might have been / Jeff Britting -- Anthem and 'the individualist manifesto' / Jeff Britting -- Anthem as a psychological fantasy / Tore Boeckmann -- Anthem in the context of related literary works : 'we are not like our brothers' / Shoshana Milgram -- 'Sacrilege toward the individual' : the anti-pride of Thomas More's Utopia and Anthem's radical alternative / John Lewis -- Needs of the psyche in Ayn Rand's early ethical thought / Darryl Wright -- Breaking the metaphysical chains of dictatorship : free will and determinism in Anthem / Onkar Ghate -- Prometheus' discovery : individualism and the meaning of the concept "I" in Anthem / Greg Salmieri -- Freedom of disassociation in Anthem / Amy Peikoff -- Anthem and collectivist regression into primitivism / Andrew Bernstein.
Includes bibliographical references (p. 325-326) and index.
Keywords: Rand, Ayn; Rand, Ayn